2010
DOI: 10.1074/jbc.m109.074617
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Degradation of α-Synuclein in Vivo

Abstract: Pathologic accumulation of ␣-synuclein is a feature of human parkinsonism and other neurodegenerative diseases. This accumulation may be counteracted by mechanisms of protein degradation that have been investigated in vitro but remain to be elucidated in animal models. In this study, lysosomal clearance of ␣-synuclein in vivo was indicated by the detection of ␣-synuclein in the lumen of lysosomes isolated from the mouse midbrain. When neuronal ␣-synuclein expression was enhanced as a result of toxic injury (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
255
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(271 citation statements)
references
References 32 publications
12
255
0
4
Order By: Relevance
“…Epidemiological studies have suggested an increased risk for PD after paraquat exposure (Hertzman et al 1990;Liou et al 1997;Kamel et al 2007;Ritz et al 2009;Tanner et al 2011). Additionally, paraquat treatment increases a-synuclein aggregates reminiscent of Lewy bodies in PD Fernagut et al 2007;Mak et al 2010). Paraquat is also reported in one study to reduce noradrenergic neurons in the locus coeruleus (Fernagut et al 2007).…”
Section: Paraquatmentioning
confidence: 90%
“…Epidemiological studies have suggested an increased risk for PD after paraquat exposure (Hertzman et al 1990;Liou et al 1997;Kamel et al 2007;Ritz et al 2009;Tanner et al 2011). Additionally, paraquat treatment increases a-synuclein aggregates reminiscent of Lewy bodies in PD Fernagut et al 2007;Mak et al 2010). Paraquat is also reported in one study to reduce noradrenergic neurons in the locus coeruleus (Fernagut et al 2007).…”
Section: Paraquatmentioning
confidence: 90%
“…Increased levels of LAMP-2A have been observed in the early stages of PD both in mouse models [54] and in brains of PD patients [52]. However, in advanced stages, reduced levels of LAMP-2A and hsc70 have been detected instead in the dopaminergic neurons of human brain regions [58].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 94%
“…Dysfunction in CMA has been described in both familial [50,52,54,55] and sporadic [51,52] PD. In the case of familial PD, sequence analysis reveals the presence of CMA-targeting motifs in the majority of PD-related proteins, supporting an important role for CMA in the control of their intracellular levels ( Figure 2A).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…TPPP/p25␣ Impairs the Autophagosomal Degradation Pathway-Aggregated or modified forms of ␣-synuclein are substrates of all major degradative systems in vivo and in vitro, including the ubiquitin proteasome system, chaperone-mediated autophagy, and macroautophagy (8,9,50,51). In this study we have used p25␣ expression as a tool to increase aggregation and autophagosomal uptake of ␣-synuclein.…”
Section: Discussionmentioning
confidence: 99%